2022
DOI: 10.37676/ekombis.v10i1.1699
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Transfer Pricing, Kepemilikan Institusional dan Kompensasi Rugi Fiskal terhadap Tax Avoidance Studi Kasus Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2015-2019

Abstract: This research was conducted to determine whether transfer pricing, institutional ownership and compensation for losses have an effect on tax avoidance in manufacturing companies listed on the Indonesia Stock Exchange in 2015-2019. This study uses descriptive statistical analysis methods and panel data regression analysis using Eviews software version 10. The sampling in this study was using purposive sampling technique so that 33 companies were obtained with an observation period of 5 (five) years. From the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
1
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 0 publications
0
1
1
6
Order By: Relevance
“…Several previous studies have examined the effect of Leverage and Profitability Fiscal Loss Compensation on Tax Avoidance. Research from Andriyani and Mahpudin (2021) shows that Fiscal Loss Compensation affects Tax Avoidance, in contrast to a study conducted by Wardana and Asalam (2022) that fiscal loss compensation does not affect Tax Avoidance. Eneksi and Shandy's research (2019) results show that leverage affects tax avoidance.…”
Section: Introductioncontrasting
confidence: 73%
See 1 more Smart Citation
“…Several previous studies have examined the effect of Leverage and Profitability Fiscal Loss Compensation on Tax Avoidance. Research from Andriyani and Mahpudin (2021) shows that Fiscal Loss Compensation affects Tax Avoidance, in contrast to a study conducted by Wardana and Asalam (2022) that fiscal loss compensation does not affect Tax Avoidance. Eneksi and Shandy's research (2019) results show that leverage affects tax avoidance.…”
Section: Introductioncontrasting
confidence: 73%
“…Fiscal losses to the company were not carried out intentionally, but losses did occur in that period. Wardana and Asalam. (2022) and Anarky and Bustari (2021) conducted study results that concluded no effect between fiscal loss compensation and tax avoidance.…”
Section: Fiscal Loss Compensation On the Effect Of Probability On Tax...mentioning
confidence: 99%
“…Transaksi hubungan istimewa berpengaruh terhadap agresivitas pajak. Transaksi hubungan istimewa merupakan kebijakan penentuan harga transfer antar transaksitransaksi kepada pihak berelasi yang sering digunakan oleh perusahaan multinasional untuk mentransfer keuntungan untuk menghindari beban pajak tanggungannya (Putri & Mulyani, 2020) Untuk meningkatkan agresivitas pajak dengan memperhatikan harga transfer, maka yang harus dilakukan oleh perusahaan adalah dengan mentrasfer hasil dari kekayaan yang dimiliki oleh perusahaan di dalam negeri dengan perantara ke perusahaan yang terdapat di luar negeri dengan tujuan untuk mendapatkan tarif pajak yang lebih kecil (Wardana & Asalam, 2022). Oleh karena itu, hipotesis yang akan diuji dalam penelitian ini adalah: H2: Transaksi hubungan istimewa berpengaruh terhadap agresivitas penghindaran pajak.…”
Section: Pengaruh Transaksi Hubungan Istimewa Terhadap Agresivitas Pe...unclassified
“…Dana APBN 80% berasal dari perpajakan yang membuktikan bahwa pajak menjadi andalan pendapatan nasional (Fatimah et al, 2021). Dalam meningkatkan penerimaan pajak pemerintah berusaha untuk menyempurnakan peraturan perpajakan yang berlaku (Wardana & Asalam, 2022). Selain itu, untuk meningkatkan penerimaan pajak daerah dapat dilakukan melalui efisiensi pemungutan pajak dan retribusi (Ruliana, 2015).…”
Section: Pendapatan Asli Daerah (Pad)unclassified